2014
DOI: 10.1038/bjc.2014.231
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of MMSET mRNA levels on survival to first-line FOLFOX and second-line docetaxel in gastric cancer

Abstract: Background:Breast cancer susceptibility gene 1 (BRCA1) expression differentially affects outcome to platinum- and taxane-based chemotherapy. Mediator of DNA damage checkpoint protein 1 (MDC1), p53-binding protein 1 (53BP1), multiple myeloma SET domain (MMSET) and ubiquitin-conjugating enzyme 9 (UBC9) are involved in DNA repair and could modify the BRCA1 predictive model.Methods:Mediator of DNA damage checkpoint protein 1, 53BP1, MMSET and UBC9 mRNA were assessed in gastric tumours from patients in whom BRCA1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…However, they did notice a strong association between mRNA expression of BIM and OS in a subset of patients who received second-line docetaxel-based chemotherapy. Similar findings have been observed in other studies [ 122 , 123 ]. This shows that the association between mRNA expression and OS in gastric cancer can be affected by chemotherapy and is also dependant on the chemotherapeutic agents used.…”
Section: Discussionsupporting
confidence: 93%
“…However, they did notice a strong association between mRNA expression of BIM and OS in a subset of patients who received second-line docetaxel-based chemotherapy. Similar findings have been observed in other studies [ 122 , 123 ]. This shows that the association between mRNA expression and OS in gastric cancer can be affected by chemotherapy and is also dependant on the chemotherapeutic agents used.…”
Section: Discussionsupporting
confidence: 93%
“…The present authors previously observed that GC patients with high BRCA1 levels could benefit from receiving second-line docetaxel-based chemotherapy (6). In addition, the median OS was further prolonged for patients with high levels of BRCA1 and multiple myeloma SET domain (39). The DNA damage caused by chemotherapy leads to cell cycle arrest, DNA repair or commitment to apoptosis (40).…”
Section: Discussionmentioning
confidence: 72%
“…Relative gene expression quantifications were calculated according to the comparative Ct method using β-actin as an endogenous control and commercial human lung and liver RNA (Stratagene, La Jolla, CA, USA) as calibrators. Final results were determined by the formula 2 -(ΔCtsample-ΔCtcalibrator) and were performed according to Technical Bulletin #2 (Applied Biosystems) ( 9 ).…”
Section: Methodsmentioning
confidence: 99%